(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The environment’s carrying capacity, which is increasingly being pressured by the population, has provided enormous space for economic needs, resulting in significant pressure on the environment. Meeting economic needs, housing has an impact on environmental problems. Furthermore, the existence of the river is essential to maintaining its sustainability. The management must be carried out in a comprehensive and integrated manner based on environmentally sound values ​​for a sustainable river function. These logical reasons, which underlie the main thoughts on river conservation, are the keywords for achieving the objectives of river regulation as stipulated through Government Regulation Number 38 of 2011, the legal and political policy directions that have been outlined for river conservation efforts, river development, and controlling the destructive power of river water. The obligation to maintain the existence of clean and environmentally sound rivers is the duty of all components of society, including policymakers and stakeholders. This responsibility is a form of legal imposition so that the legal order can achieve the goals of justice for the environment because rivers have a significant role in the sustainability of a balanced life.